Molecular signatures of host specificity linked to habitat specialization in Exaiptasia sea anemones. Issue 11 (30th April 2018) - Bellis, Emily S.; Edlund, Reid. B.; Berrios, Hazel K.; Lessios, Harilaos A.; Denver, Dee R.
Abstract: Rising ocean temperatures associated with global climate change induce breakdown of the symbiosis between coelenterates and photosynthetic microalgae of the genus Symbiodinium . Association with more thermotolerant partners could contribute to resilience, but the genetic mechanisms controlling specificity of hosts for particular Symbiodinium types are poorly known. Here, we characterize wild populations of a sea anemone laboratory model system for anthozoan symbiosis, from contrasting environments in Caribbean Panama. Patterns of anemone abundance and symbiont diversity were consistent with specialization of holobionts for particular habitats, with Exaiptasia pallida / S. minutum (ITS2 type B1) abundant on vertical substrate in thermally stable, shaded environments but E. brasiliensis / Symbiodinium sp. (ITS2 clade A) more common in shallow areas subject to high temperature and irradiance. Population genomic sequencing revealed a novel E. pallida population from the Bocas del Toro Archipelago that only harbors S. minutum . Loci most strongly associated with divergence of the Bocas‐specific population were enriched in genes with putative roles in cnidarian symbiosis, including activators of the complement pathway of the innate immune system, thrombospondin‐type‐1 repeat domain proteins, and coordinators of endocytic recycling. Our findings underscore the importance of unmasking cryptic diversity in natural populations and the role of long‐term evolutionary history in mediating interactions with Symbiodinium . Abstract : The sea anemone Exaiptasia pallida (commonly known as Aiptasia ) is increasingly studied as a laboratory model system for understanding symbioses with dinoflagellate algae ( Symbiodinium ); however, little is currently known regarding fine‐scale genetic variation in natural populations. This study provides the first genome‐scale view of Exaiptasia population structure at the center of holobiont diversity, at locations along the Caribbean coast of Panama where extensive long‐term environmental monitoring datasets are available. We discovered a novel population of E. pallida that exhibits strong differentiation from the globally distributed host population at candidate loci involved in mediating symbiotic interactions with Symbiodinium, providing new targets for further study on the cellular dynamics of cnidarian symbiosis.